Hopes and dreams: poverty, motherhood and health care - Pope, Bonnie; Bloom, Kathaleen (International Journal of Advanced Nursing Studies, 2016)
Racial and ethnic differences in health outcomes exist in all areas of health care even when factors related to income; insurance status and access to care are controlled. The importance of the social environment versus biological influences a personâ€™s health status are explored in this study. Healthy People 2020 identified maternal health status to pregnancy-related health outcomes and African American women are at greater risk for poor pregnancy outcomes including increased rates of maternal, perinatal, neonatal, and infant mortality.Study Purpose: To understand the meaning of being and African-American woman living in poverty and their experiences with the health care system. Research Design: Exploratory qualitative, community-based participatory action research study used oral and digital storytelling. Participants and Setting: African American mothers residing in government subsidized housing.Data Collection and Analysis: Focus groups, storytelling, and photovoice for data collection. Thematic analysis the focus groupsâ€™ transcriptions and storyboard findings was conducted. Results: Common themes from the transcripts were â€œrespect meâ€¦donâ€™t stereotype meâ€ and â€œbe safe.â€ Themes from storyboards were â€œlove of family,â€ â€œlove of community,â€ and â€œhope for the future.â€ Courage, family, and community are the foundation of their lives. Limitation: Sample size does not allow generalization to larger populations.Â